2016
DOI: 10.21873/anticanres.11102
|View full text |Cite
|
Sign up to set email alerts
|

Neurofibromin Expression is Associated with Aggressive Disease and Poor Outcome in Colorectal Carcinoma

Abstract: Abstract. Aim: To assess the predictive and prognostic value of neurofibromin (NF) expression in colorectal carcinoma (CRC). Materials and Methods: The present series consists of archival samples from 191 patients with stage I, II, III, or IV CRC treated between 1981 and Colorectal cancer (CRC) is the third most common cancer in the world, also ranking as the third most common cause of cancer-related deaths (1). Despite the fact that most CRC patients undergo potentially curative surgery and adjuvant chemothe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 11 publications
1
4
1
Order By: Relevance
“…As all the patients in our cohort were diagnosed with high-risk NBL, all of our results on NF1 correspond to the hypothesis on the relationship between NF1 overexpression associated with aggressive tumor behavior. Similar findings were recently published for colorectal carcinoma (29).…”
Section: Discussionsupporting
confidence: 91%
“…As all the patients in our cohort were diagnosed with high-risk NBL, all of our results on NF1 correspond to the hypothesis on the relationship between NF1 overexpression associated with aggressive tumor behavior. Similar findings were recently published for colorectal carcinoma (29).…”
Section: Discussionsupporting
confidence: 91%
“…Similar to their CRC samples, we had nearly 80% of the samples with moderate (score 2) to strong (score 3) staining intensity (Figure 3). While in other series, COX2 expression was not significantly different among tumour grades [12,47], a significant enrichment of poorly differentiated tumours was observed among COX2-negative samples in our study. Different studies reported higher OS rates among CRC patients whose tumours are negative for COX2 protein [24,28,30,36,47,59].…”
Section: Cdx2 and Mcrc Clinical Outcomescontrasting
confidence: 92%
“…Prostaglandins (PGs) play a predominant role in cancer development through promoting cell proliferation, invasion, angiogenesis and immunosuppression. 10 The COX-2-regulated synthesis of PGs, particularly PGE-2, causes various types of cancers including CRC. 11 COX-2 gene is highly expressed in 85% of adenocarcinoma cases with a poor survival rate.…”
Section: Introductionmentioning
confidence: 99%